Upaya Meningkatkan Kompetensi Guru, Konsentrasi, dan Kemampuan Bahasa Anak melalui Metode Bermain Tepuk di Kelompok Bermain XYZ - Chicilia Nurhayati; Nancy Susianna (Syntax Corporation Indonesia, 2024)
Student learning concentration, student language skills, and teacher competency are very important in achieving student development in early childhood education. These three competencies in the XYZ Playgroup Class in Jakarta have not been well developed. This research aims to analyze the effectiveness of the clapping playing method on teacher competence, the development of student learning concentration, improving students' language skills, as well as the implementation of the learning process in the classroom. The research method used is classroom action research which includes three cycles, each cycle includes the stages of planning, observation, action and reflection. The research subjects were 16 students, two observers. The research instrument is an assessment rubric to measure teacher competency, student learning concentration, and student learning ability. The research results showed that teacher competency increased from Cycle 1 to Cycle 2 with an N-Gain of 03, but from Cycle 2 to Cycle 3 there was no increase because the N-Gain value was still the same (0.3). Meanwhile, the comparison of teacher competency from Cycle 1 to Cycle 3 achieved good development, because the N-Gain value reached 0.6. Student learning concentration has increased, as can be seen from the N-Gain from Cycle 1 to Cycle 2, an increase of 0.4 was obtained. Then the N-Gain from Cycle 2 to Cycle 3 obtained an increased value of 0.6. Students' language skills experienced an increase in N-Gain from Cycle 1 to Cycle 2, resulting in an increase of 0.4. Then the N-Gain from Cycle 2 to Cycle 3 obtained an increased value of 0.5.